Efektivitas Penyediaan Air Bersih dalam Memenuhi Kebutuhan Masyarakat oleh Pemerintah Nagari Gunuang Malintang Kabupaten Lima Puluh Kota - Hidayatullah, M. Alfin; Malau, Hasbullah (Lembaga Yasin AlSys, 2025)
Limited provision of clean water in rural areas continues to face various geographical, technical, and institutional constraints, including in Nagari Gunuang Malintang, particularly Jorong Batu Balah. This study aimed to analyze the effectiveness of clean water provision by the Nagari Gunuang Malintang government in meeting community needs and to identify the factors that influence the effectiveness of its implementation. A qualitative approach was employed, with data collected through in-depth interviews, field observations, and document study. Research informants included the Wali Nagari, nagari government officials, clean water supply program implementers, relevant experts, and beneficiary communities in Jorong Batu Balah. The findings show that the clean water supply program has reached 270 out of 281 households; however, service effectiveness remains low due to a system that is unable to meet demand during peak hours, weak water pressure in higher elevation areas, and unstable flows that reduce community satisfaction and disrupt residents’ daily activities. Program effectiveness has not been optimal because of limited infrastructure capacity, the absence of water quality testing in accordance with health standards, budget constraints, and geographical as well as system maintenance challenges. The study concludes that effective and sustainable clean water provision in Nagari Gunuang Malintang requires strengthening technical and institutional aspects and cross-sector collaboration so that clean water services can meet community needs more equitably and reliably.